Neuroscientific evidence for multisensory convergence and interaction - Emi Tanaka; Tetsuo Kida; Ryusuke Kakigi; Minoru Hoshiyama (Japanese Society of Physical Fitness and Sports Medicine, 2017)
Effective behaviors optimized for various situations are enabled by various sensory information. How does the brain deal simultaneously with information from different sensory systems? Investigation of multisensory processing began from neuroanatomical and neurophysiological studies at the level of single neurons. Accumulation of knowledge concerning neurons and progress in recording techniques of human brain activity have led to a massive expansion in recent neuroscientific studies using various combinations of brain activity recording and cognitive tasks. In this paper, we briefly review recent neuroscientific studies related to multisensory convergence and interaction, focusing on electrophysiological and imaging studies in humans.